Recreational water monitoring: Nanofluidic qRT‐PCR chip for assessing beach water safety. Issue 4 (25th September 2019) - Shahraki, Abdolrazagh Hashemi; Heath, Daniel; Chaganti, Subba Rao
Abstract: Improved recreational water monitoring using rapid molecular genetic methods would decrease both public health risks and unnecessary beach closures. Hence, we developed a novel nanofluidic quantitative real‐time PCR (qPCR) in the OpenArray platform to (a) detect and quantify fecal indicator bacteria (FIBs; N = 2), (b) identify contaminant sources (microbial source tracking (MST); N = 7), and (c) detect human virulent pathogens (virulence gene markers; N = 15). Our water monitoring OpenArray plate reliably detects as few as two template copies/hole (OpenArray ® well), with some marker sensitivities as low as single‐copy detection. The OpenArray plate showed high target sequence specificity and returned expected patterns of contaminants for fecal and sewage samples. We found Canada geese and seagulls were the leading causes of contamination at beaches that tested positive for coliforms. When we incorporated robotic DNA extraction, we were able to process samples from water to FIBs, MST, and waterborne pathogen detection and quantification within four hours. Our monitoring TaqMan qPCR assays in the OpenArray platform is uniquely valuable for regulatory agencies charged with beach water safety as well as for researchers interested in human health implications of aquatic microbial community structure. Abstract : Water quality monitoring is done using the coliform count as an indicator of human fecal matter contamination in the recreational water. However, coliforms were not a appropriate indicators as they can grow in the environment. So we have developed an alternative markers, which can used to detect the source of contamination as well as pathogen detection. The methods developed in the current study are rapid and inexpensive and can be directly applied for recreational monitoring programs.